2013
DOI: 10.1093/nar/gkt1219
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of p53 response elements in solution deduced using site-directed spin labeling and Monte Carlo sampling

Abstract: The tumor suppressor protein p53 regulates numerous signaling pathways by specifically recognizing diverse p53 response elements (REs). Understanding the mechanisms of p53-DNA interaction requires structural information on p53 REs. However, such information is limited as a 3D structure of any RE in the unbound form is not available yet. Here, site-directed spin labeling was used to probe the solution structures of REs involved in p53 regulation of the p21 and Bax genes. Multiple nanometer distances in the p21-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…, base and shape readout, also known as direct and indirect readout [55]) were often historically presented as mutually exclusive driving forces for DNA recognition by a given protein. Only recently have structural studies [19, 56, 57] embraced the more realistic situation that most proteins use the interplay of base and shape readout to recognize their cognate binding sites. The contributions of base and shape readout, however, vary across protein families (Figure 2C; Figure 3).…”
Section: Transcription Factors Recognize Dna Through the Interplay Ofmentioning
confidence: 99%
“…, base and shape readout, also known as direct and indirect readout [55]) were often historically presented as mutually exclusive driving forces for DNA recognition by a given protein. Only recently have structural studies [19, 56, 57] embraced the more realistic situation that most proteins use the interplay of base and shape readout to recognize their cognate binding sites. The contributions of base and shape readout, however, vary across protein families (Figure 2C; Figure 3).…”
Section: Transcription Factors Recognize Dna Through the Interplay Ofmentioning
confidence: 99%
“…Previously reported acquisition parameters and procedures [29] were used with slight modifications ( d 1=200 ns instead of 128 ns). Specifically, a dead-time-free four-pulse scheme was used, [30] with the pump pulse frequency set at the center of the nitroxide spectrum and the observer frequency at approximately 70 MHz higher.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to note that, in SDSL studies, the number of distances measured is relatively small. However, a number of studies have shown that with careful design of experiments these “sparse” long-range constraints can be highly informative (Duss, Michel, et al, 2014; Duss, Yulikov, Allain, & Jeschke, 2015; Duss, Yulikov, Jeschke, & Allain, 2014; Hirst, Alexander, McHaourab, & Meiler, 2011; Zhang et al, 2014, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In this chapter, we describe an integrated SDSL/computational-modeling approach that we have developed for mapping an RNA junction (Zhang et al, 2012) and examining sequence-dependent conformations of DNA duplexes (Chen et al, 2013; Zhang et al, 2014). This approach builds upon an SDSL tool kit previously developed and validated (Qin et al, 2007), which includes three components: (i) a nucleotide-independent nitroxide probe, designated as R5, that can be efficiently attached at defined sites within arbitrary nucleic acid sequences (Fig.…”
Section: Introductionmentioning
confidence: 99%